Hepatocyte growth factor enhances the clearance of a multidrug‐resistant Mycobacterium tuberculosis strain by high doses of conventional chemotherapy, preserving liver function. Issue 2 (8th July 2019) - Bello‐Monroy, Oscar; Mata‐Espinosa, Dulce; Enríquez‐Cortina, Cristina; Souza, Verónica; Miranda, Roxana U.; Bucio, Leticia; Barrios‐Payán, Jorge; Marquina‐Castillo, Brenda; Rodríguez‐Ochoa, Ignacio; Rosales, Patricia; Gutiérrez‐Ruiz, María Concepción; Hernández‐Pando, Rogelio; et al.
Abstract: Tuberculosis (TB) is one of the deadliest infectious diseases in humankind history. Although, drug sensible TB is slowly decreasing, at present the rise of TB cases produced by multidrug‐resistant (MDR) and extensively drug‐resistant strains is a big challenge. Thus, looking for new therapeutic options against these MDR strains is mandatory. In the present work, we studied, in BALB/c mice infected with MDR strain, the therapeutic effect of supra‐pharmacological doses of the conventional primary antibiotics rifampicin and isoniazid (administrated by gavage or intratracheal routes), in combination with recombinant human hepatocyte growth factor (HGF). This high dose of antibiotics administered for 3 months, overcome the resistant threshold of the MDR strain producing a significant reduction of pulmonary bacillary loads but induced liver damage, which was totally prevented by the administration of HGF. To address the long‐term efficiency of this combined treatment, groups of animals after 1 month of treatment termination were immunosuppressed by glucocorticoid administration and, after 1 month, mice were euthanized, and the bacillary load was determined in lungs. In comparison with animals treated only with a high dose of antibiotics, animals that received the combined treatment showed significantly lower bacterial burdens. Thus, treatment of MDR‐TB with very high doses of primary antibiotics particularly administrated by aerial route can produce a very good therapeutic effect, and its hepatic toxicity can be prevented by the administration of HGF, becoming in a new treatment modality for MDR‐TB. Abstract : HGF protects the liver from anti‐tuberculosis drugs toxicity HGF potentiates the pharmacological effects of anti‐tuberculosis drugs HGF differentially modulates ROS content in the liver and the lungs